Conceptual framework of authentic chemistry problem-solving competency among school students - Muhamad, Suraiya (2015)
This paper discusses the conceptual framework of authentic chemistry problem solving competency in learning electrolysis. Authentic learning practice has a potential to improve problem solving competency by creating a meaningful learning environment among school students. This conceptual framework incorporates two established models; model of problem solving instruction: Search, Solve, Create and Share (Pizzini, 1987) and model of authentic learning (Herrington, 2000) with Science Framework in Program for International Student Assessment (PISA) by The Organization for Economic Cooperation and Development (2012). Authentic practice in learning chemistry will enhance higher order thinking skills especially to solve the open-ended problems. Open-ended problem is an ill-defined and non-routine problem, which is presenting a real-life context that interesting and relevant to the students.Student’s prior scientific knowledge competency, experience, problem solving skill and authentic learning practice are identified to be the independent variables to develop problem solving competency in learning chemistry. Chemistry problem solving ability test and problem solving skills questionnaire are administered to 112 full reseidential school students. Result from the preliminary study found that low (20.5%) and average(53.6%) achiever in Chemistry problem solving ability test has verified the independent variables are essential for the research. Domains in the problem solving skills are also at the average and low level. This framework is being implemented in a research being undertaken at present. The research will be investigating the impact of module of the authentic learning practice on the chemistry problem-solving competency among full residential school students.